Structure and corrosion resistance of cerium-oxide films on AZ31 as deposited by high-power ultrasound supported conversion chemistry - Liu, Chen-Ni; Wiesener, Markus; Giner, Ignacio; Grundmeier, Guido (Frontiers in Materials, 2015)
In the present study a conversion layer mainly composed by ceria oxide was prepared by means of a novel ultrasound assisted coating process. The formation of a conversion layer on top of the Mg alloy provides physical barrier properties improving the corrosion protection. In addition the incorporation of cerium oxide within the coating enables the formation of a protective layer on the pores and defect inhibiting localized corrosion. The chemical composition of the conversion layer was evaluated by means of Raman spectros-copy, FT-IR spectroscopy and XPS. The prepared porous films were rich in Ce4+ and featured a very low content of oxygen deficient cerium oxide. FE-SEM measurements were performed in order to assess the morphology of the prepared coating revealing homogeneous and uniform surfaces. Self-repair ability was verified by monitoring capacitance of the system after polarization by means of electrochemical impedance spectroscopy. Additional, Raman spectroscopic measurements showed presence of cerium ions in defect sites which may suggest self-repair mechanism.